2014
DOI: 10.1016/j.icarus.2014.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and radial trends in Saturn’s thermal plasma between the main rings and Enceladus

Abstract: a b s t r a c tA goal of Cassini's extended mission is to examine the seasonal variations of Saturn's magnetosphere, moons, and rings. Recently we showed that the thermal plasma between the main rings and Enceladus exhibited a time dependence that we attributed to a seasonally variable source of oxygen from the main rings (Elrod, M.K.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 30 publications
0
20
0
1
Order By: Relevance
“…The strong correlation between the F EUV and the plasma density is somewhat surprising since earlier studies have suggested that a varying photoionization rate due to the changing solar EUV flux alone could not result in such large variations as the one seen in Figures and , (e.g., Elrod et al, ). To estimate the change in density due to the changing solar EUV flux, we derive the photoionization rate coefficients κ j , where j = 1,2,3,4, corresponding to (1) the larger flux at date 30 June 2005, (2) the smaller flux at 30 June 2009, (3) larger flux at 30 June 2015, and (4) smaller flux at 30 June 2016.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…The strong correlation between the F EUV and the plasma density is somewhat surprising since earlier studies have suggested that a varying photoionization rate due to the changing solar EUV flux alone could not result in such large variations as the one seen in Figures and , (e.g., Elrod et al, ). To estimate the change in density due to the changing solar EUV flux, we derive the photoionization rate coefficients κ j , where j = 1,2,3,4, corresponding to (1) the larger flux at date 30 June 2005, (2) the smaller flux at 30 June 2009, (3) larger flux at 30 June 2015, and (4) smaller flux at 30 June 2016.…”
Section: Resultsmentioning
confidence: 86%
“…As the particles are transported outward, due to collisional interactions, a seasonal variation could also be expected in the particle densities in between the main rings and Enceladus. A seasonal variation was also found in the CAPS n i (Elrod et al, , ) and the RPWS n e (Persoon et al, ). With the 11 years RPWS/LP data set we can now extend the results of these studies and also investigate the solar cycle modulation of Saturn's inner plasma disk.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Johnson et al () computed a photolytic flux of 10 6 /cm 2 s for neutral O 2 emission from the rings from solar ultraviolet irradiation but found the radiolytic flux from GCR interaction products to be an order of magnitude lower. However, strong seasonal variability up to several orders of magnitude (Christon et al, , ; Elrod et al, , ) of the magnetospheric O 2 + and other heavy ion population beyond the rings argues against the GCR energy source that varies only slightly over decadal time scales at energies above 20 GeV. Roussos et al () report long‐term changes of CRAND proton fluxes by less than a factor of 2 during the Cassini mission; the GCR flux at the ring neutron source for CRAND in the radiation belts would vary comparably.…”
Section: Discussionmentioning
confidence: 99%